Gendering bodies - Crawley, Sara L., 1966- (Gender lens series., 2008)
Gendering Bodies explains how the social world shapes our physical bodies and how our bodies shape the social world. In this remarkable investigation into contemporary ideas of gender, sociologists Crawley, Foley, and Shehan argue that bodies are constantly being gendered, that is, encouraged to participate in (heterosexual) gender conformity. This engendering influences nutrition practices, work and employment choices, diet, exercise, cosmetic surgery, sexual practices, and training - or lack thereof - in sports and fitness. This is an accessible, yet comprehensive, sociological inquiry into a theory of the gendered body.